Penatalaksanaan Periodontitis Apikalis pasca Restorasi Inadekuat pada Gigi Anterior Mandibula - Aryadi; Stefani, Rosita; Ratnasari, Dina; Tjingson, Natalia (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Inadequate dental restorations may disrupt the coronal seal and permit microleakage, allowing bacterial penetration into the root canal system. Persistent microbial contamination can induce a host-mediated inflammatory response in the periapical tissues, resulting in apical periodontitis. Root canal treatment is indicated to eliminate intracanal infection through effective cleaning, shaping, and disinfection, thereby supporting periapical healing. Objective: This case report describes the endodontic management of chronic apical periodontitis associated with an inadequate restoration in a mandibular anterior tooth, highlighting the clinical decision-making and treatment protocol to achieve periapical healing. Case report: A 34-year-old female patient presented to RSGM FKG USAKTI, with a chief complaint of a dislodged restoration on her lower left anterior tooth, which had been restored approximately one year prior. Intraoral examination revealed a cavity on the disto-palatal surface of tooth 32. Radiographic examination showed caries reaching the pulp on the distal surface, accompanied by apical periodontitis. At the initial visit, caries removal, access cavity preparation, and biomechanical preparation of the root canal system were performed. Root canal obturation was completed at a subsequent visit, followed by placement of a definitive direct composite resin restoration one month later. Conclusion: Multi-visit root canal treatment followed by definitive composite resin restoration was successfully performed, demonstrating effective management of apical periodontitis secondary to inadequate restoration in a mandibular anterior tooth.